Post-stroke Dysphagia: Recent Insights and Unanswered Questions - Jones, Corinne A. (Curr Neurol Neurosci Rep, 2020)
PURPOSE OF REVIEW: We explored themes in recent post-stroke dysphagia literature, focusing on the following questions: (1) What does post-stroke dysphagia look like?; (2) Who gets post-stroke dysphagia?; (3) What are the consequences of post-stroke dysphagia?; and (4) How can we improve treatment of post-stroke dysphagia? RECENT FINDINGS: There have been several improvements in quantitative descriptions of swallowing physiology using standard and new evaluation techniques. These descriptions have been correlated with lesion locations, and several factors can predict development of post-stroke dysphagia and its sequelae. Novel treatment paradigms have leveraged post-stroke neuroplastic improvements using neurostimulation and biofeedback techniques. Despite recent findings, the field is limited by lack of standardization and unanswered questions on rehabilitation variables. SUMMARY: Our improved understanding of post-stroke dysphagia will enhance our ability to prevent, identify, and treat it. Future work should be grounded in swallowing physiology and continue refining treatments, particularly in the acute stage.